Modifying biodegradable plastics with additives based on condensed tannin esters. Issue 11 (7th November 2014) - Grigsby, Warren J.; Bridson, James H.; Schrade, Carmen
ABSTRACT Condensed tannins derived from Pinus radiata bark have been esterified and added to biodegradable plastics as extrusion compounded functional plastic additives. The presence of longer alkyl chain hexanoate esters promoted tannin miscibility in the commercial polyesters Bionolle™ and Biopol™ whereas short chain acetate esters tended to remain as discrete domains, acting as fillers in the processed plastics. In the aliphatic polyester Bionolle the presence of tannin esters at typical plastic additive loadings did not alter plastic mechanical properties whereas at 5% content in Biopol the tannin‐additives reduced both flexural and tensile properties. Similarly tannin esters do not alter the melt or glass transition temperatures of the polyesters, but tannin hexanoate at 5% can influence the crystallization temperatures. Artificially aging plastics realized the functionality these plant extracts can impart to plastics in acting to reduce ultraviolet (UV)‐induced plastic degradation. Results indicate the tannin‐additives likely provide a stabilising role through inhibiting UV penetration into the plastic, with color analysis suggesting the tannin moiety itself was sacrificial and preferentially degrading. The imparted UV stability was linked to the dissolution of tannin esters in the plastic with longer chain esters providing greater protection against UV degradation. Tannin esters showed potential as functional additives for biodegradable polymers enhancing the UV stability of the plastic. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41626.